Penerapan Modul Point of Sale Odoo untuk Efisiensi Transaksi Penjualan UMKM Toko Tiga Saudara - Shafira, Hurul Aini; Amalia; Suhendi (LPPM STT Terpadu Nurul Fikri, 2025)
This study aims to implement the Point of Sale (PoS) module system using Odoo for the micro, small, and medium enterprise (MSME) Toko Tiga Saudara, which currently relies on a manual recording system. Manual data recording often leads to various issues such as data loss, calculation errors, delays in report generation, and difficulties in accurately monitoring inventory. Therefore, an integrated and efficient system solution is required. The research method used is qualitative with an action research approach. Data were collected through in-depth interviews and direct observations of the store owner and daily operational activities. The implementation process included installing Odoo, configuring the PoS module based on the store’s requirements, conducting user training, performing system testing using the User Acceptance Testing (UAT) method, and evaluating system effectiveness. The results show that the system is capable of integrating transaction processes and inventory management in real time, minimizing recording errors, and generating accurate and easy-to-understand sales reports. Furthermore, the system increases operational efficiency and supports the store owner in making strategic decisions. The implemented system is deemed to meet the user’s needs; however, further development is recommended to add additional features that can support business growth in the future.